Espaço político e sindicalismo: a posição política das lideranças sindicais em João Pessoa/PB. - Barreto, Maria de Fátima (2010)
The political space is complex and multidimensional. On one side it is defined through the relationships between the voters and political parties or the political-ideological proposals of a certain political system. On the other hand it is a subjective space where they are the representations that the citizens do of the political phenomenon in the own way that each one internalizes the effective ideologies in a certain society. (Carvalho, Lima & Camino, 2005). Objectively they are found the spectra of antagonistic ideological positions forming a polarized space and multi-dimensional. This polarization is represented by several dyads, among them, left-right. (Bobbio, 2001). Inserted in the supporting and syndical political historical process, the political positioning acquires certain complexity that needs elucidation. With this I aim at, this research tried to analyze and to describe the representations of the left, related with the syndical and supporting identity starting from the positioning in the political space of João Pessoa-Paraíba's syndical leaderships. The research was accomplished with syndical directors, interviewed individually, in the headquarters of the unions. A Free Association following by the questionnaire was applied. The analyses of the results (n = 210) they were distributed in five categories. The largest and priority indicators of the syndicalists' associated to the left representations are in the visions more politicized, related to the activist-opposition ones and to the classists. The medium score of importance indicated as main priority of the left association in the syndicalists' mind the syndical movement, socialism, conflicts between workers and bosses and the organization activate of the syndical movement. In relation to the supporting and syndical identity, the data revealed that PT and CUT, traditional vehicles of the left, received to total and accentuated sympathy of the vision ativist/oposicionist and accentuated antipathy of the classists. CONLUTAS and INTERSINDICAL was with to strong antipathy of the activist-opposition vision and strong sympathy of the classists. It is observable in these data, an opposition tendency inside of the own syndical movement, where a group is looking for a new alternative for the organization syndical classist. The results also revealed that the left concept is still quite reasonable to analyze the political spectrum. What evidenced this fact was the majority left positioning found especially among the syndicalists of the visions more politicized. However, it is observable a gradual rejection of that classic spectrum in the measure in that there is a great group presenting a vision negative evaluation of the left concept and other group that it didn't accept none of the positionings politician.